2019
DOI: 10.1249/mss.0000000000001833
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Spontaneous Baroreceptor Sensitivity after Concussion

Abstract: Introduction Cardiovascular autonomic nervous system (CV-ANS) function is negatively impacted after concussion. The arterial baroreflex buffers pressor and depressor challenges through efferent modulation of cardiac chronotropism and inotropism, and peripheral vascular tone. Baroreceptor sensitivity (BRS) reflects the capacity of the CV-ANS to accommodate dynamic metabolic demands in the periphery. The impact of concussion on BRS has yet to be defined. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…With sports being such a popular activity for health, social, and psychological reasons, sport-related concussion and its potential long-term effects remain a major health problem [1]. Sport-related concussion and mild traumatic brain injury (mTBI) have been used synonymously and previous research has documented physiological changes post-injury [2,3,4,5]. Concussion has been defined as a “complex pathophysiological process affecting the brain, induced by traumatic biomechanical forces …” [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With sports being such a popular activity for health, social, and psychological reasons, sport-related concussion and its potential long-term effects remain a major health problem [1]. Sport-related concussion and mild traumatic brain injury (mTBI) have been used synonymously and previous research has documented physiological changes post-injury [2,3,4,5]. Concussion has been defined as a “complex pathophysiological process affecting the brain, induced by traumatic biomechanical forces …” [6].…”
Section: Introductionmentioning
confidence: 99%
“…These affects can in turn distort neuronal membrane permeability [7]. The exact pathophysiology of mTBI is not fully understood, but it has been suggested that autonomic dysfunction [2,5] and changes in total blood volume and cerebral blood flow do occur [3,8]. Although mTBI is generally associated with autonomic-like symptoms [9], no single objective diagnostic test can determine concussion severity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…62 Concussion can initiate a neurometabolic cascade, 63 which can lead to an energy crisis, thereby impairing cerebral blood flow, 64 increasing intracellular calcium (Ca 2+ ) levels, 63,65 and disrupting autonomic functioning, 66,67 among other physiological consequences ( Figure 1). 63,66,[68][69][70][71][72][73][74][75][76] mTBIs generally occur due to rotational or twisting forces (accelerations or decelerations) 77,78 of the brain within the skull, thereby resulting in a disruption in homeostasis. In comparison, the endocannabinoid system is thought to have neuroprotective properties, 79,80 which could therefore ameliorate these disturbances in physiological homeostasis.…”
Section: Concussion Implication and Endocannabinoid Neurophysiology Imentioning
confidence: 99%